The Influence of Leadership, Work Environment, Job Satisfaction, Work Discipline on Employee Performance at The Office Of Population Control and Familiy Planning (DPPKB) District Labuhanbatu - Abdul Leman Lubis; Bayu Eko Broto; Christine Herawati Limbong (PT Mattawang Mediatama Solution, 2023)
The purpose of this study was to determine the effect of leadership, work environment, job satisfaction, work discipline on employee performance at the office of population control and family planning (DPPKB) Labuhanbatu regency. The population and sample in this study were all 40 DPPKB employees. The research method uses multiple linear regression analysis which is processed using SmartPLS3. The results of the study prove that the independent variable (X), namely leadership, work environment, job satisfaction and work discipline both partially and simultaneously have a positive and significant effect on employee performance. The R square value is 0.799 or 79,90%, the variable leadership, work environment, job satisfaction and work discipline afeect employee performance, while the remaining 20,10% is influenced by other factors such as work motivation, work enthusiasm, work ethic, skills, and compensation